Propos sur le change étranger et la réassurance - Parizeau, Gérard; Obadia, Armand (Assurances)

(untitled) (HEC Montréal, 1985)
Fluctuations in foreign exchange rates are not a reinsurance problem as such. However, when these are substantial from one year to the next, they must be taken seriously. In trying to show why, the authors of this article point out, for example, how excellent underwriting results can, in fact, become disastrous, or, on the other hand, be even better than expected. lndeed, exchange rates are so important that insurers should take measures to protect themselves against sizeable, unexpected losses, year after year, when one currency is exchanged for another.